Second workshop of climate-smart agriculture prioritization framework in Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The CSA Prioritization Framework, developed by CCAFS-CIAT, provides a process for targeting investment towards best-bet CSA options in a given context. The Framework does this by identifying existing and promising CSA practices, assessing the tradeoffs between practices using indicators of CSA and analyzing the costs and benefits of these practices, and identifying possible barriers to adoption. This process aims to contribute to optimized national and sub-national planning, promoting a participatory process for the development of CSA investment portfolios. Photos: J.L.Urrea (CCAFS)